Razmerje med izbrisnim in kondikcijskim zahtevkom - Vodopivec, Katarina (Pravnik, 2015)
The author deals with institutes of action for striking out and condiction, assert claims for assumptions of erased application and application of condiction. The author derives its assumptions from the authoritative normative regulatory that is not regulated by law. At the same time, the author deals with the institute of unjust enrichment. Review of suitability to assert application of condiction by a recent case-law is also presented. In the article the author also considerates the problem of special issues about the obligation of returning the assets, for which the contracting part was unjustly enriched.
Keywords: sodišča; sodna praksa; sodne odločbe